ANALISIS PERCEPATAN PELAKSANAAN DENGAN MENAMBAH JAM KERJA OPTIMUM PADA PROYEK KONSTRUKSI (Studi Kasus: Proyek Pembangunan Super Villa, Peti Tenget-Badung) - Frederika, Ariany (Jurnal Ilmiah Teknik Sipil, 2012)
In the implementation of construction projects, there is often a discrepancy between the planned schedules and the work in the field, thus causing delays. Many factors cause a delay, one way to anticipate is by doing the acceleration. In doing acceleration, cost and quality factors must be considered in order to obtain the optimum cost and quality standards desired. Super Villa Development Projects is selected for research studies because of delays in its implementation. Alternative acceleration used is the addition of working hours, from one hour to four hours without any additional manpower. The calculation begins by finding the critical path using Microsoft Project and then crashing is carried out to obtain cost slope activities that are on critical path, then the analysis is performed using Time Cost Trade-Off Analysis. Finally, a graphic of the relationship between the cost and the optimum time for each additional hour of work is created. From the analysis results, the optimum cost is obtained by adding one hour of works which reduce cost and time of Rp784,104.16 and eight days respectively, while the optimum time is obtained at additional two hours, with a reduction time of 14 days and cost reduction of Rp700,377.35. This means that the acceleration with optimum cost is obtained when the addition is of one hour of work and optimum time is obtained when the addition is of two hours of work.
Keywords: acceleration, Microsoft Project, critical path, cost slope, time cost trade off analysis, optimum.